2005
DOI: 10.1002/chin.200507087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oxazolidinones and 1,2‐Diamines from N‐Alkyl Aziridines.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the late 20 th and early 21 st Century, numerous metal complexes and salts such as LiI [24,25] (2, Scheme 3), alkali metal halides [26] (3, Scheme 3) and organotin complexes [27] (4, Scheme 3) were the first metal catalysts tested in the transformation of CO2 into oxazolidinones. These catalysts required high catalytic loadings (at least 25 mol% in the case of LiI), high pressures of CO2 (50-55 bar in the case of organoantimony salts) and reported poor isomer selectively.…”
Section: Homogenous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 20 th and early 21 st Century, numerous metal complexes and salts such as LiI [24,25] (2, Scheme 3), alkali metal halides [26] (3, Scheme 3) and organotin complexes [27] (4, Scheme 3) were the first metal catalysts tested in the transformation of CO2 into oxazolidinones. These catalysts required high catalytic loadings (at least 25 mol% in the case of LiI), high pressures of CO2 (50-55 bar in the case of organoantimony salts) and reported poor isomer selectively.…”
Section: Homogenous Catalystsmentioning
confidence: 99%
“…In 2008, Li performed detailed DFT analysis [42] of the reaction mechanism between aziridines and CO2 conversion into oxazolidinones, via Pinhas's LiI catalytic route. [24,25] Li concluded that changing alkyl substituents on the three membered ring strongly affects regioselectivity, whereas changing groups on the nitrogen atom seemed to have little to no effect at all. [42] Li proposed that when simple alkyl groups are present on the three membered ring (with functional groups on the nitrogen) ring-opening only occurs at the less sterically hindered carbon-nitrogen bond.…”
Section: Mechanism Considerationsmentioning
confidence: 99%